Comparison of biofloc formation from microalgal cultivation by auto- and bacteria-associated types of flocculation - Ngoc Thu, Tran Thi; Dong Phuong, Nguyen Thi; Van Luan, Tran; Van Anh, Le Thi (Vietnam Journal of Biotechnology, 2023)
Microalgal harvesting has still been a challenge to investigators who take their investiment into microalgal production. The cost for microalgal downstream processing is as high as 20% of the total production of biodiesel. Among hundreds of curent methods of biomass harvesting, autoflocculation and bacteria-based aggregation are still being researched and applied in large-scale producuion. This study implemented a comparison of how microalgal cells aggregate large bioflocs according to two types of flocculation. The microalgal autoflocculation was implemented by adding Ca2+ or Mg2+ with an increase of pH to 11, resulting in cell biomass of 13.7 or 15.5 mg/l, respectively. Meanwhile, the bioflocculation under the support of Bacillus subtilis MT300405 and Escherichia coli ATCC 85922 could produce large bioflocs with a cell biomass of 1.5 times higher than the autoflocculation case without the influence of pH. Moreover, images from scanning electron microscopy indicated differences between two types of flocculation. With the presence of bacteria, microalgal cells were more tightly bound by a membrane or a layer of extracellular polimeric substance, inducing to form large bioflocs. This was not found under autoflocculation.